Influence of operation parameters on the shaping of the denitrification communities in full-scale municipal sewage treatment plants. (October 2020) - Castellano-Hinojosa, A.; Maza-Márquez, P.; González-López, J.; Rodelas, B.
Highlights: Genes of the denitrification pathway were quantified by qPCR in 4 full-scale WWTPs. narG absolute and relative abundances were always greater than those of napA . The absolute and relative abundances of norB were higher in the anoxic bioreactors. nosZ I was more abundant than nosZ II in 3 of the 4 WWTPs analysed. Most denitrification genes were more abundant with longer SRT and higher NO3 − & NO2 − . Abstract: The abundances of the napA, narG, nirK, nirS, norB, nosZ I and nosZ II genes, involved in all the steps of the bacterial denitrification pathway, were monitored by a quantitative PCR approach in 4 municipal wastewater treatment plants (WWTPs). The absolute and relative abundances of narG were greater than those of napA in all the surveyed facilities, while few significant differences were found in the case of the nitrite reductase genes nirK and nirS . Greater absolute and relative abundances of the norB gene were always detected in the anoxic bioreactors, and the nosZ I gene was more abundant than nosZ II in 3 of the WWTPs analysed. Gene abundances were significantly linked to the variations of the operating parameters and environmental conditions influencing the WWTPs, using multivariate analysis. Taken together, the solids retention time (SRT), and the concentrations of nitrite (NO2 − ) and nitrate (NO3 − ) in the activated sludge were the major abiotic variables explaining the ordination of samples. These results contribute to understand the shifts of the different groups of denitrifying bacteria in activated sludge, seeking for operation strategies allowing to maximise N removal without increasing nitrous oxide (N2 O) emissions.